Millman's electronic devices and circuits - Millman, Jacob (Tata McGraw-Hill, 2007)
Millman's electronic devices and circuits / Millman, Jacob. -- New Delhi: Tata McGraw-Hill, 2007 621.38132 M655e2 2nd ed. No. of Copies : 1